2010
DOI: 10.1071/ah09655
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and health: an exploratory study of hospital patients' perspectives

Abstract: The relationship between spirituality/religion and health is receiving increasing academic interest, but few studies have explored the experience of Australians. This paper presents data from an exploratory survey of patients and families in a public teaching hospital in Sydney. The findings show that the majority of hospital service users:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…While Australia has yet to explore whether or not belief God or a higher power is related to mental health, particularly in the context of mental health patients and psychiatric treatment outcomes, the papers sourced with data collection in this search do, however, appear to show that spirituality and religion can be important, prevalent and relevant in mental health care settings. For instance, Hilbers et al (2010) survey revealed that 75% of the participants said spirituality or religious beliefs of some kind religion were important to them, and over 80% thought their health was affected by spiritual and religious beliefs. In addition, spirituality could provide protection in times of crisis by providing another perspective on the meaning of life, as Wilding (2007) found in selected interviews.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While Australia has yet to explore whether or not belief God or a higher power is related to mental health, particularly in the context of mental health patients and psychiatric treatment outcomes, the papers sourced with data collection in this search do, however, appear to show that spirituality and religion can be important, prevalent and relevant in mental health care settings. For instance, Hilbers et al (2010) survey revealed that 75% of the participants said spirituality or religious beliefs of some kind religion were important to them, and over 80% thought their health was affected by spiritual and religious beliefs. In addition, spirituality could provide protection in times of crisis by providing another perspective on the meaning of life, as Wilding (2007) found in selected interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Patient Religiosity was also measured in Payman et al (2008) study on depressed elderly Australians by the Duke University Religion Index (Koenig, George, & Peterson, 1997) -this five item scale asked about frequency of religious attendance, frequency of participation in private religious activities such as prayer, meditation, or Bible study, and intrinsic religiosity which asks patients to rate themselves to these questions: "My religious beliefs are what really lies behind my whole approach to life," "I try hard to carry my religion over into all other dealings in life," and, "In my life, I experience the presence of the Divine." Hilbers et al (2010) sample consisted of hospital patients. The study used a survey instrument that comprised of 18 core items to assess the importance of spirituality, most of which were phrased as closed-choice statements which were available in English, Chinese, Arabic and Greek.…”
Section: Mental Health Religion and Culturementioning
confidence: 99%
See 3 more Smart Citations